Community-Based Waste Management at Al-Rosyid Islamic Boarding School, Mpokdamira Ngumpakdalem Village and Gayam Village, Bojonegoro Regency - Muhajirin, Ahmad; Kusuma, Maritha Nilam (IDFoS Indonesia, 2021)
The purposes of this assistance were to increase the capacity of the waste community in managing domestic waste, including communication, coordination and initial assessment of domestic waste management with stakeholders, preparation of a sustainable waste management plan, implementation of provision waste management facilities in the community, the integration of community waste management with stakeholders, implementation of management (sorting and processing of waste). The method used was Participatory Action Research (PAR). The results of the assistance carried out were a change in the pattern of waste management in Mpokdamira, which initially used organic waste as liquid organic fertilizer, and it became solid organic fertilizer with better quality, the existence of waste management activities at the Al Rosyid Islamic Boarding School by maximizing the role of TPD and TPS, able to operate machines with better fuel quality, the emergence of impacts due to changes in clean and healthy living behavior on the environment of each program, as well as increasing the capacity of the waste community in managing domestic waste.